Longitudinal patterns of behaviour problems in children with specific speech and languge difficulties: child and context factors - Lindsay, G; Dockrell, J; Strand, S (Wiley, 2007)
Background: The purpose of this study was to examine the stability of behavioural, emotional and social difficulties (BESD) in children with specific speech and language difficulties (SSLD), and the relationship between BESD and the language ability. Methods: A sample of children with SSLD were assessed for BESD at ages 8, 10 and 12 years by both teachers and parents. Language abilities were assessed at 8 and 10 years. Results: High levels of BESD were found at all three ages but with different patterns of trajectories for parents' and teachers' ratings. Language ability predicted teacher- but not parent-rated BESD. Conclusion: The study confirms the persistence of high levels of BESD over the period 8-12 years and the continuing comorbidity of BESD and language difficulties but also indicates a complex interaction of within-child and contextual factors over time.